2014
DOI: 10.1103/physreva.89.052514
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic atom-surface interactions in the Casimir-Polder regime

Abstract: The distance-dependence of the anisotropic atom-wall interaction is studied. The central result is the 1/z 6 quadrupolar anisotropy decay in the retarded Casimir-Polder regime. Analysis of the transition region between non-retarded van der Waals regime (in 1/z 3 ) and Casimir-Polder regime shows that the anisotropy cross-over occurs at very short distances from the surface, on the order of 0.03λ, where λ is the atom characteristic wavelength. Possible experimental verifications of this distance dependence are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Somers and Munday found that, for particular orientations of optical axes, the Casimir force can be repulsive, even when the two anisotropic slabs are identical [17]. In recent years, scientists have started to investigate the interaction between anisotropic particles and a surface [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somers and Munday found that, for particular orientations of optical axes, the Casimir force can be repulsive, even when the two anisotropic slabs are identical [17]. In recent years, scientists have started to investigate the interaction between anisotropic particles and a surface [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous works [9][10][11][12][13][14][15][16][17][18][19] only focused on the anisotropy of the plates and assumed that the space between the two plates was a vacuum or was filled with isotropic materials. However, in fact, this region could also be anisotropic.…”
Section: Introductionmentioning
confidence: 99%
“…Ran Zeng and his collaborators investigated the Casimir force between anisotropic single-negative metamaterial slabs and show that the electromagnetic responses of the metamaterial parallel and perpendicular to the optical axis affected the Casimir force differently [13]. Recent years, the research works have extended to the interaction between anisotropic particles and a surface [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Again a laser beam is an efficient tool for this purpose and its interaction with atoms could be accurately characterized by means of the present MC-code. Actually any configuration combining resonant light and atoms is relevant (provided that the semi-classical approximation is valid), in particular the use of a "pushing" laser to generate a slow atomic beam from a magneto-optical trap, a technique which has been successfully tested with metastable argon atoms [36].…”
Section: Resultsmentioning
confidence: 99%